Revolutionizing cancer treatment with Halomonas Aquamarina L-Glutaminase: insights from in vitro and computational studies - Sara Abdelsayed; Alaa Elmetwalli; Jihan Hassan; Mohamed O. Abdel Monem; Ali H. El-Far; Fuad Ameen; Mervat G. Hassan (Scientific Reports)
Abstract Bacterial L-glutaminase (L-GLS) has emerged as a potential therapeutic target in cancer treatment by disrupting glutamine-dependent metabolic pathways in tumor cells. This study focused on isolating and characterizing L-GLS-producing marine bacteria from Mediterranean seawater for preliminary therapeutic evaluation. Halomonas aquamarina HBIM1 was identified as the most efficient isolate through comprehensive phenotypic, genotypic, and enzymatic screening. The enzyme was successfully purified, achieving a specific activity of 748.35 U/mg with 3.39-fold purification. SDS-PAGE analysis confirmed high purity with a single 66 kDa protein band. Kinetic characterization revealed optimal activity at pH 8 and 50 °C, with strong substrate affinity (Km = 0.198 mM⁻¹). Preliminary in vitro cytotoxicity screening demonstrated selective antiproliferative effects on HepG2 liver cancer cells (IC50 = 33.98 µg/ml) compared to normal WI-38 cells (IC50 = 93.43 µg/ml), yielding a 2.75-fold selectivity index. Molecular docking analysis identified tannic acid and 6-diazo-5-oxo-L-norleucine as selective inhibitors of bacterial L-GLS, with tannic acid showing the highest binding affinity (-12.25 kcal/mol) and 5-fold selectivity over human L-GLS, suggesting potential for combination therapy strategies. These proof-of-concept findings indicate the preliminary anticancer potential of Halomonas-derived L-GLS and computational support for selective inhibitor development. However, comprehensive preclinical validation, including in vivo efficacy studies, toxicological evaluation, and pharmacological profiling, is essential to establish therapeutic viability and safety before clinical consideration.